Examine the Prevalence of Hepatitis C Virus in Multi-Transfused Thalassemia Major Patients - Huda Khalid Safi, Awais Tanveer, Saba Hammad, Anum Nadeem, Shaheera Nadeem, Amina Asif, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To examine the prevalence of Hepatitis C virus in multi-transfused thalassemia major patients and risk factors associated with HCV infection. Study Design: Cross-sectional/Observational Place and Duration: Department of Medicine/ Haematology, Lahore General Hospital, Lahore, Pakistan for the duration of six months from March 2021 to August 2021. Methods: One hundred and sixty five multi-transfused patients of β thalassemia major were enrolled in this study. After taking informed consent patients’ demographics including age, sex, socioeconomic status, residence and blood transfusion frequency were recorded. Blood sample was taken from all the patients to examine the seroprevalence of Hepatitis C virus by using ELISA method. Data was analyzed by SPSS 24.0. Results: There were 113(68.48%) males and 52 (31.52%) female patients. 71 (43.03%) patients were ages >10 years and 94 (56.97%) patients were ages <10 years. 48 (29.09%) patients were found to have HCV positive. Among HCV positive patients males were predominant 33 (68.75%), 37 (77.08%) patients had above 15 transfusion and 11 (22.92%) had less than 15 transfusion. Patients with low socio-economic status were on high risk for developing HCV infection. Conclusion: It is concluded that Hepatitis C virus is significantly associated with multi-tranfused Beta thalassemia major. The frequency of HCV infection is quite high. Keywords: Multi-transfusion, Beta Thalassemia Major, Hepatitis C virus